Potential microgrid model based on hybrid photovoltaic/wind turbine/generator in the coastal area of North Sumatra - Habib Satria; Rahmad Syah; Dadan Ramdan; Muhammad Khahfi Zuhanda; Jaka Windarta; Syafii Syafii; Almoataz Youssef Abdelaziz (Institute of Advanced Engineering and Science, 2024)
The high potential for renewable energy in the North Sumatra region, especially the coast of the Belawan area, needs to be exploited properly. The design that will be carried out is to explore the potential in coastal areas by simulating microgrid systems and hybrid system-based electricity installations. The method that will be used is to find the accuracy of strategic location points by considering the panel surface temperature which will later influence the power output of the power plant. Then find the ideal installation location as a reliable system when irregular climate conditions occur, of course this phenomenon will have a significant effect on energy balance and energy conversion, especially in coastal areas. The potential for installation construction will be carried out with a hybrid system using power sources from photovoltaics, wind turbines and diesel generators assisted by HOMER Pro software. The results of testing with simulations and information data that have been recorded in the software can later be used as a benchmark in planning electrical installations and also for identifying microgrid protection challenges. Then the measurement results that have been obtained for the installation of a hybrid-based microgrid system on Photovoltaic (PV) are DC output power of 618.80 W with measurements of sunny weather conditions, then the potential wind speed on the wind turbine reaches 5 m/s and the potential use of a diesel generator reaches 40% with power output capacity 1 kW.